Emission Trading Systems in Indonesia’s Power Generation Sub-Sector:Comparative Analysis, Governance Failures, and Policy Recommendations - Paul Patar Maruli Butarbutar; Muhammad Zilal Hamzah; Eleonora Sofilda (Testing Center for Oil and Gas LEMIGAS, 2026)
Indonesia’s Emission Trading System (ETS) for the power generation sub-sector is a central instrument for achieving its Nationally Determined Contribution (NDC) targets, yet critical governance failures undermine its environmental and fiscal effectiveness. A significant gap in the existing literature concerns how long-term contractual provisions in power markets interact with ETS compliance obligations, and whether those interactions systematically undermine the polluter-pays principle. This study employs a qualitative multi-method design combining comparative institutional analysis of ETS frameworks in the European Union, China, and Indonesia with primary data from an expert Focus Group Discussion (FGD) of six informants, coded using NVivo 12 qualitative software. The study identifies two structural governance failures. First, the ETS is operationally voluntary: the penalty regulation mandated by Law No. 7/2021 has not been issued by the Ministry of Finance, eliminating the compliance incentive. Second, a Government Force Majeure (GFM) clause embedded in Power Purchase Agreements (PPAs) between the state utility PT PLN and Independent Power Producers (IPPs) creates a multi-stage fiscal pathway through which ETS compliance costs may be transferred from coal-fired power plant operators to the state energy subsidy budget — structurally inverting the polluter-pays principle. Comparative analysis further reveals that while Indonesia’s intensity-based ETS shares design features with China’s national carbon market, it lacks the enforcement architecture that China has progressively established. The study contributes a novel governance failure mode — the GFM–ETS fiscal compensation pathway — not previously theorised in ETS governance literature, and recommends enforcement regulation issuance, GFM–subsidy fiscal interface reform, integrated MRV platform development, bottom-up cap-setting anchored in plant-level data, and establishment of a dedicated carbon market authority.